Prognostic and immunological implications of cathepsin Z overexpression in prostate cancer - Tao, Junyue; Chen, Yiding; Bian, Xiaokang; Cai, Tingting; Song, Changhao; Liang, Chaozhao; Hao, Zongyao; Meng, Jialing; Ge, Qintao; Zhou, Jun (Frontiers in Immunology, 2025)
BackgroundRecent studies have underscored the potential involvement of cathepsin Z (CTSZ) in modulating the progression of diverse tumor types. Nevertheless, its specific role in prostate cancer (PCa) remains insufficiently understood. This study aimed to investigate the expression profile of CTSZ in PCa and evaluate its prognostic significance.MethodsThree independent cohorts, including TCGA-PRAD, MSKCC, and a real-world AHMU-PC cohort were enrolled in this study. Multidimensional strategies consist of spatial transcriptome analysis, differential expression analysis, survival analysis, and correlation with clinicopathological features were performed. Immunohistochemical staining and multiplex immunofluorescence staining were performed to evaluate the expression and spatial distribution of CTSZ and immune-related markers in PCa tissues. Functional studies were conducted through a series of experiments, including CCK-8 assay, colony formation, wound healing, and Transwell migration assays. ssGSEA and CIBERSORT algorithms immune infiltration evaluation, and GISTIC2.0 and MutSigCV for tumor mutation burden. Gene Set Enrichment Analysis was performed to identify potential signaling pathways involved.ResultsCTSZ is highly expressed in PCa tissues and is associated with higher Gleason scores, advanced T/N staging, and poor prognosis. Survival analyses across multiple cohorts indicate that high CTSZ expression predicts shorter progression-free survival and overall survival. In vitro experiments showed that CTSZ knockdown suppresses PCa cell proliferation, invasion, migration, and colony formation. Immune profiling revealed that high-CTSZ tumors exhibit an immune-enriched microenvironment, characterized by increased infiltration of regulatory T cells and M2 macrophages, suggesting an immunosuppressive state. Notably, despite this phenotype, PD-1 and PD-L1 levels were also elevated in high-CTSZ tumors, indicating a potential role in immune checkpoint regulation. Additionally, high CTSZ expression was correlated with increased tumor mutation burden, particularly enriched for TP53 and SPOP mutations. GSEA identified CAM, VEGF, and STAT signaling pathways as potential mechanisms through which CTSZ promotes tumor progression, highlighting its potential as both a prognostic biomarker and therapeutic target in PCa.ConclusionsOur study highlights CTSZ as a potential prognostic and therapeutic biomarker in PCa, demonstrating that its overexpression is associated with immune cell infiltration, immune checkpoint molecule expression (such as PD-1 and PD-L1), tumor mutation burden, and key oncogenic pathways. These findings suggest that CTSZ may serve not only as a predictor of patient prognosis but also as a promising indicator for immunotherapy response and personalized treatment strategies in PCa.